Resilience as a Mediator Between Interpersonal Risk Factors and Hopelessness in Depression - Collazzoni, Alberto; Stratta, Paolo; Pacitti, Francesca; Rossi, Alessandro; Santarelli, Valeria; Bustini, Massimiliano; Talevi, Dalila; Socci, Valentina; Rossi, Rodolfo (Frontiers in Psychiatry, 2020)
Several studies investigated the role of resilience as a mediating factor for psychopathological phenotypes. The aim of the current study is to explore the putative role of resilience as a mediator between different vulnerability factors and depressive symptoms. One hundred and fifty patients with a major depressive disorder diagnosis have been evaluated on the basis of humiliation (Humiliation Inventory), adverse past family experiences (Risky Family Questionnaire), hopelessness (Beck Hopelessness Scale), and resilience (Resilience Scale for Adult) scores. A multiple regression analysis and a bootstrapping method were carried out to assess the hypothesis that resilience could mediate the relationships between these risk factors as predictors and hopelessness as a dependent variable. Our results show that resilience has a mediating role in the relationship between several risk factors that are specifically involved in interpersonal functioning and hopelessness. The limitations of the study are the cross-sectional nature of the study, the use of self-report instruments, the lack of personality assessment, and the consideration of the resilience as a unique construct. The understanding of the mechanisms through which resilience mediates the effects of different interpersonal risk factors is crucial in the study of depression. In fact, future prevention-oriented studies can also be carried out considering the mediating role of resilience between interpersonal risk factors and depressive symptoms.